Tarcza Kołowa pod Wpływem Działania Siły Skupionej i Obciążenia Ciągłego // Pierścień Kołowy pod Wpływem Działania Danego Obciążenia - F. Szelągowski (Engineering Transactions, 1958)
This paper contains first the derivation of equations determining the stresses Rθ, R, and θθ at any point of a circular disc with two continuously distributed loads q and p acting on the periphery and then - the derivation of the analogous equations for a concentrated load Q and a continuously distributed load p.